DEICTIC GESTURE DALAM PENDEKATAN SAINTIFIK PADA PEMBELAJARAN MATEMATIKA UNTUK MENOPANG MINAT DAN BERPIKIR KREATIF SISWA SMP - Edi Sudrajat; Sugiatno Sugiatno; Hamdani Hamdani (Universitas Tanjungpura, 2020)
AbstractThe research objective was to reveal the dectic gesture in the scientific approach to learning mathematics towards students' creative thinking and interest at the Cahaya Kemuliaan High School for the academic year 2019/2020. The form of research is Pedagogical Action Research (PTP). The research procedure consists of three stages, namely: preparation, implementation, and final. The results of the content and empirical validity obtained that the questionnaire instruments, pretest questions, and post-test questions were feasible to be used to conduct research. After conducting the research, it was concluded that deictic gesture in the scientific approach had an influence on interest, namely on indicators of feelings of pleasure, interest and attention. Meanwhile, creative thinking is the indicator of fluency and flexibility. .Keywords: Deictic Gesture, the scientific approach, learning mathematics, Creative thinking, interest